Reviewing the Correlation of Fish Quality Alteration and In-Package Headspace Composition: Evidence From a pH Freshness Indicator Case Study - Evgenia Basdeki; Stamatia Eleni Vasilaki; Matteo Sensi; Emmanouil Flemetakis; Fabio Biscarini; Deborah Power; Theofania Tsironi (International Journal of Food Science)
Smart packaging is a continuously evolving sector that may provide solutions to several cold chain management challenges and shows great potential toward food waste reduction. Fish is a highly nutritious yet perishable commodity with increasing statistics of annual loss and waste. This study investigates the application of pH-sensitive indicators on fish products, aiming to analyze and highlight the importance of comprehensive monitoring of the physicochemical alterations and their interactions with the headspace composition during refrigerated storage of fresh fish. Insights into this process can contribute to developing more practical spoilage indicators and dynamic shelf life prediction methods. A brief case study is presented on the development and application of a smart indicator prototype. The freshness pH indicator was prepared by incorporating methyl red into a starch and cellulose matrix using the dip coating method and was tested for its sensitivity to pH, ammonia vapor, and the detection of gilthead sea bream spoilage. The deterioration in the quality of sea bream fillets, as indicated by the observed color change of the indicator, was confirmed through microbiological and chemical analyses of the fish flesh. The color response of the pH indicator (red–pink turned pale yellow) was found to correlate with fish alteration patterns and reflected the headspace gas composition thus enabling “real-time” monitoring of fish spoilage.